Effects of Safety Climate and Employee Engagement towards Organisational Citizenship Behaviour of Sewage Workers - Suryani Maryam,; Ernie Tisnawati Sule,; Joeliaty,; Rina Novianty Ariawaty, (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study aims to investigate the effects of safety climate and employee engagement on organisational citizenship behaviour (OCB). Design/Methodology/Approach: Drawing from the social exchange theory and flow theory, a theoretical framework was developed and tested using data collected from 610 freelance sewage workers. A questionnaire survey was used to collect the data, while structural equation modelling (SEM) analysis was used as the data analysis approach. Research findings: The results reveal that both safety climate and employee engagement have significantly positive impact on employees’ organisational citizenship behaviour amongst sewage workers in Indonesia. This finding indicates that although the sewage cleaners are often employed based on contract and may not be in a position to demand more from the organisations, they do appreciate the organisational commitment in producing a safe workplace environment. They, in return will demonstrate a higher engagement towards their work. Theoretical contribution/Originality: This study contributes to the organisational citizenship behaviour literature by examining how workplace environmental factors such as safety climate affects organisational citizenship behaviour. In the context of sewage cleaning, safety climate is important, as sewage workers are frequently exposed to and threatened by serious health problems. Yet, there has been a paucity of research on the sewage cleaning sector to understand the relationships. Research limitation/Implications: The study implies that when organisations are willing to improve safety climate, their employees will perceive improved safety climate, and then will have more engagement and organisational citizenship behaviour. Keywords: Safety Climate, Employee Engagement, Organisational Citizenship Behaviour, Sustainable Development Goals, Occupational Hazards JEL Classification: M12, M54, M59, J28